The Practice of Industrial Relations - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1978)
This article reviews "The Practice of Industrial Relations" by D. A. Peach and D. Kuechle.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z